(untitled) (Web of Teachers: Inderscience Research, 2025)
Education plays a crucial role in the moral, intellectual, and physical development of individuals. It helps young people find their place in society, make sound decisions, and manage their behavior. The main objective of education is to cultivate the younger generation in terms of moral and cultural values. This process is not limited to imparting knowledge, but also shaping a person’s character. The use of historical monuments, literature, art, and other cultural heritage tools enhances the educational process by providing not only academic knowledge but also fostering moral, spiritual, and aesthetic values. This article highlights the advantages of utilizing cultural heritage in education, such as fostering national pride, strengthening historical memory, shaping universal values, encouraging creativity, and promoting a sense of responsibility towards society. Educating through cultural heritage tools helps develop well-rounded individuals who respect their roots, appreciate diversity, and contribute positively to society.